Accounting reforms: A case study of Dewan Bandaraya Kuching Utara (DBKU) / Abang Iskandar Bolhassan Abang Mohammad Ariff - Abg Mohammad Ariff, Abang Iskandar Bolhassan (2015)
This dissertation examines organisational change in a Malaysian local council using Dewan Bandaraya Kuching Utara (DBKU) as the case study. Specifically, this dissertation examines the process of accounting reforms in DBKU. This dissertation also identifies the factors influencing accounting reforms in a organisation. This dissertation employs semi-structured interview and content analysis on 10 respondents who are currently employees in the finance department. Drawing from the institutional theory comprising of coercive, mimetic and normative isomorphism, this dissertation found that accounting reformation has led DBKU to achieve several recognitions particularly, during the financial and management audit.